Data‐driven regions of interest for longitudinal change in three variants of frontotemporal lobar degeneration. Issue 4 (23rd March 2017) - Binney, Richard J.; Pankov, Aleksandr; Marx, Gabriel; He, Xuanzie; McKenna, Faye; Staffaroni, Adam M.; Kornak, John; Attygalle, Suneth; Boxer, Adam L.; Schuff, Norbert; Gorno‐Tempini, Maria‐Luisa; Weiner, Michael W.; et al.
Abstract: Introduction: Longitudinal imaging of neurodegenerative disorders is a potentially powerful biomarker for use in clinical trials. In Alzheimer's disease, studies have demonstrated that empirically derived regions of interest (ROIs) can provide more reliable measurement of disease progression compared with anatomically defined ROIs. Methods: We set out to derive ROIs with optimal effect size for quantifying longitudinal change in a hypothetical clinical trial by comparing atrophy rates in 44 patients with behavioral variant of frontotemporal dementia (bvFTD), 30 with the semantic variant primary progressive aphasia (svPPA), and 26 with the nonfluent variant PPA (nfvPPA) to atrophy in 97 cognitively healthy controls. Results: The regions identified for each variant were generally what would be expected from prior studies of frontotemporal lobar degeneration (FTLD). Sample size estimates for detecting a 40% reduction in annual rate of ROI atrophy varied substantially across groups, being 103 per arm in bvFTD, 31 in nfvPPA, and 10 in svPPA, but in all groups were less than those estimated for a priori ROIs and clinical measures. The variability in location of peak regions of atrophy across individuals was highest in bvFTD and lowest in svPPA, likely relating to the differences in effect size. Conclusions: These findings suggest that, while cross‐validated maps of change can improve sensitivity to change in FTLD compared with a priori regions, the reliability of these maps differs considerably across syndromes. Future studies can utilize these maps to design clinical trials, and should try to identify factors accounting for the variability in patterns of atrophy across individuals, particularly those with bvFTD. Abstract : This work describes a process for creating optimized data‐driven regions of interest (ROIs) for measuring change in cortical volume in three major variants of frontotemporal lobar degeneration. Estimated sample sizes that should be achievable using these ROIs are compared with sample sizes for tracking change in clinical variables.